Analisis Hambatan Proses Pembelajaran IPS Secara Daring Pada Kelas IVa SDN Baros Kencana CBM - Antari Dea Mariam; Arsyi Rizqia Amalia; Astri Sutisnawati (STKIP Andi Matappa Pangkep, 2020)
This study aims to analyze the IPS learning process online and the obstacles of the IPS learning process online. This research was conducted at Baros Kencana Public Elementary School CBM which was calculated from May to early July. This research uses descriptive qualitative research methods. The subjects of study were students in grade 4a at SDN Baros Kencana CBM. Data collection techniques in this study used semi-structured interviews, open questionnaires of Google forms and documentation. The results of research that has been done that the impact of the epidemic covid-19 has an influence on the learning process. The solution for learning to be carried out even in situations at home by holding an online learning process. The online learning process is felt to be less effective for teachers and students. The teacher is not free in delivering the material, the assignment is not in accordance with the material presented. Teachers have difficulty in processing student grades during online learning. Not all students have communication tools that support online learning. Other barriers experienced by students during the online learning process students do not understand the assignments because they are not explained beforehand and students feel bored while carrying out online learning.